The novel sustained 3‐hydroxybutyrate donor poly‐D‐3‐hydroxybutyric acid prevents inflammatory bowel disease through upregulation of regulatory T‐cells. Issue 1 (23rd December 2022) - Suzuki, Rimina; Mishima, Mayuko; Nagane, Masaki; Mizugaki, Hinano; Suzuki, Takehito; Komuro, Mariko; Shimizu, Takuto; Fukuyama, Tomoki; Takeda, Shiro; Ogata, Masaya; Miyamoto, Takayoshi; Aihara, Naoyuki; et al.
Abstract: Inflammatory bowel disease (IBD) is a chronic persistent intestinal disorder, with ulcerative colitis and Crohn's disease being the most common. However, the physio‐pathological development of IBD is still unknown. Therefore, research on the etiology and treatment of IBD has been conducted using a variety of approaches. Short‐chain fatty acids such as 3‐hydroxybutyrate (3‐HB) are known to have various physiological activities. In particular, the production of 3‐HB by the intestinal microflora is associated with the suppression of various inflammatory diseases. In this study, we investigated whether poly‐D‐3‐hydroxybutyric acid (PHB), a polyester of 3‐HB, is degraded by intestinal microbiota and works as a slow‐release agent of 3‐HB. Further, we examined whether PHB suppresses the pathogenesis of IBD models. As long as a PHB diet increased 3‐HB concentrations in the feces and blood, PHB suppressed weight loss and histological inflammation in a dextran sulfate sodium‐induced IBD model. Furthermore, PHB increased the accumulation of regulatory T cells in the rectum without affecting T cells in the spleen. These results indicate that PHB has potential applications in treating diseases related to the intestinal microbiota as a sustained 3‐HB donor. We show for the first time that biodegradable polyester exhibits intestinal bacteria‐mediated bioactivity toward IBD. The use of bioplastics, which are essential materials for sustainable social development, represents a novel approach to diseases related to dysbiosis, including IBD.